the Religious Factors That Created The Partition Between India and Pakistan - Saumi, Raihana Putri (Islamic Research, 2025)
This research aims to describe the historical background of the separation between India and Pakistan. Descriptive qualitative is used as a method of this research with a data collection method in the form of content analysis so that the author can analyze the origin of the separation of India and Pakistan through historical documents, documentary films, and related historical writings. The results of the analysis found that the main cause of this tragedy was the problem of Islam and Hinduism that had occurred long before Christ, where India and Pakistan, the majority of Hindus and Muslims, had a grudge against one another, they felt they had authority, felt superior to each other as during the reign of one of the kings of the Mughal dynasty leaders who applied dictatorial rules that made Hindus feel depressed and Islam, which was a minority, felt unsafe and received treatment that was deemed inappropriate, as a result both parties suppressed religious freedom and committed violence to be superior and were supported by the political factor of British colonization. This was followed by a massive migration in 1947, said to be the bloodiest migration in the world, due to rampant violence, killings and thefts totaling millions of deaths.